Histomorphometrical Analysis of Coronary Atherosclerosis Lesions Formation in Rat (Rattus norvegicus) Model - Rheza Permana; Fatkhur Rizqi; Ardian Pradana; I Dewa A. Susilawati; Tantin Ermawati (Faculty of Dentistry, Universitas Indonesia, 2014)
<!--[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Cardiovascular disease is the most deadly disease in the world and the main cause is atherosclerosis. New paradigm explains that chronic inflammation such as periodontitis is considered to be a risk factor for atherosclerosis. Periodontitis causes bacteremia affecting vascular inflammation. This situation affects the endothelial cells and lipid oxidation thereby increasing the risk of atherosclerosis. This study aimed to prove the effect of periodontitis on coronary atherosclerotic lesion formation. Methods: This was an experimental study using the post-test only control group design. Samples were 12 rats divided into control group (K) without treatment and periodontitis (P) was made with the installation of wire ligature and injection of Porphyromonas gingivalis on the left mandibular M1 for 28 days. On day 29, mice were decaputated, coronary artery was taken and histological slides were made. Histomorphometrical analysis was calculated on dungkul (descriptive) and the thickness of the arterial wall (with test statistic T test). Results: The results showed higher formation of arterial dungkul on Periodontitis group (83.33%) than the control group (16.67%). Arterial wall was also thicker periodontitis group (2.22±0.35μm) (p<0.05) than the control group (1.28±0.20μm). Conclusion: Periodontitis can independently affect the coronary atherosclerotic lesion formation. DOI: 10.14693/jdi.v20i3.198 <!--[if gte mso 9]> <w:LsdException Locked="false" Priority="63" SemiHidden="false" UnhideWhenUsed="false" Name="Medium